Poly(acrylic) nanocoatings deposited by AP-PECVD processes on paper substrates for packaging applications - García, José Manuel; Mota, Jordi; Crespo, Laia; Martínez, Meritxell; Aubouy, Laurent; Bautista, Llorenç (International Conference on Plasma Surface Engineering, 2013)
Poly(acrylic acid) coatings on paper substrates have been prepared by atmospheric pressure plasma enhanced chemical vapor deposition (AP-PECVD). The structure/properties relationships of the samples were studied in dependence of the plasma experimental conditions. Acrylic acid monomer/helium ratio and treatment speed clearly influences the wettability properties of the paper substrate: advancing contact angle values were reduced to the half (around 60 º) if compare to non-treated paper (120 º approximately). The surface morphology of the films did not greatly vary with the plasma polymerization treatment.